Probiotics in milk replacer affect the microbiome of the lung in neonatal dairy calves - McDaneld, Tara G.; Eicher, Susan D.; Dickey, Aaron; Kritchevsky, Janice E.; Bryan, Keith A.; Chitko-McKown, Carol G. (Frontiers in Microbiology, 2024)
Probiotics have been investigated for their many health benefits and impact on microbiota of the gut. Recent data have also supported a gut-lung axis regarding the bacterial populations (microbiomes) of the two locations; however little research has been done to determine the effects of oral probiotics on the microbiome of the bovine respiratory tract. We hypothesized that probiotic treatment would result in changes in the lung microbiome as measured in lung lavage fluid. Our overall goal was to characterize bacterial populations in the lungs of calves fed probiotics in the milk replacer and dry rations from birth to weaning. A group of 20 dairy calves was split into two treatment groups: Probiotic (TRT; N = 10, milk replacer + 5 g/d probiotics;Bovamine Dairy, Chr. Hansen, Inc., Milwaukee, WI) and Control (CON; N = 10, milk replacer only). On d 0 birth weight was obtained and calves were provided colostrum as per the dairy SOP. On d 2, probiotics were added to the milk replacer of the treated group and then included in their dry ration. Lung lavages were performed on d 52 on five random calves selected from each treatment group. DNA was extracted from lavage fluid and 16S ribosomal RNA (rRNA) gene hypervariable regions 1 through 3 were amplified by PCR and sequenced using next-generation sequencing (Illumina MiSeq) for identification of the bacterial taxa present. Taxa were classified into both operational taxonomic units (OTUs) and amplicon sequence variants (ASVs). Overall, evaluation of these samples revealed that bacterial genera identified in the lung lavage samples of probiotic-fed calves as compared to the control calves were significantly different based on the OTU dataset (P < 0.05) and approached significance for the ASV dataset (P < 0.06).Additionally, when comparing diversity of taxa in lung lavage samples to nasal and tonsil samples, taxa diversity of lung samples was significantly lower (P < 0.05). In conclusion, analysis of the respiratory microbiome in lung lavage samples after probiotic treatment provide 3 insight into the distribution of bacterial populations in response to oral probiotics and demonstrates that oral probiotics affect more than gut microbiome.